2015
DOI: 10.1017/s0954579415000413
|View full text |Cite
|
Sign up to set email alerts
|

Variation in serotonin transporter linked polymorphic region (5-HTTLPR) short/long genotype modulates resting frontal electroencephalography asymmetries in children

Abstract: Previous studies have documented the serotonin transporter linked polymorphic region (5-HTTLPR) as a genetic susceptibility variant that contributes to variability in outcomes related to affective psychopathology, with the short allele associated with negative affectivity and the long allele associated with positive affectivity. In a separate but related line of research, extensive evidence suggests that frontal electroencephalography (EEG) hemispheric asymmetry in the alpha band is also associated with risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 83 publications
1
9
0
Order By: Relevance
“…Overall EEG alpha power has stronger genetic effects than asymmetry measures (heritability of 79–85% across all regions) [van Beijsterveldt and van Baal, ]. Candidate gene studies have found support for greater right frontal asymmetry (in some regions) in child and adult carriers of the 5‐HTTLPR S allele [Bismark et al, ; Christou et al, ]. Other serotonergic genes have also been studied, with a polymorphism in HTR1A (rs6295; G allele) predicting greater right asymmetry across almost all frontal regions, while a variant in HTR2A was associated with right asymmetry in only one region [Bismark et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall EEG alpha power has stronger genetic effects than asymmetry measures (heritability of 79–85% across all regions) [van Beijsterveldt and van Baal, ]. Candidate gene studies have found support for greater right frontal asymmetry (in some regions) in child and adult carriers of the 5‐HTTLPR S allele [Bismark et al, ; Christou et al, ]. Other serotonergic genes have also been studied, with a polymorphism in HTR1A (rs6295; G allele) predicting greater right asymmetry across almost all frontal regions, while a variant in HTR2A was associated with right asymmetry in only one region [Bismark et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…Forty-nine children from Caucasian ancestry participated in the study (24 males; 25 females; M age in months = 60.26, SD = 11.80, age range: 4–7 years of age). Participants were recruited through a local community research participation advertisement/outreach program at the local University from a pool of 70 children that have originally genotyped for the needs of previous neuroimaging genetics study on our lab (Christou et al, 2015 ). Parents or guardians of all participants reported that the child had no history of a neurological or psychiatric disorder, with normal or corrected to normal vision.…”
Section: Methodsmentioning
confidence: 99%
“…These alleles produce three genotypes (short/short, short/long, long/long). In combination with exposure to life-threatening situations, individuals carrying at least one copy of the Short allele have been reported to be at increased susceptibility for negative cognitive, behavioral, and neurophysiological outcomes [Caspi et al, 2003 ; Mercer et al, 2012 ; Xie et al, 2012 ; Disner et al, 2013 ; see also Boll and Gamer ( 2014 ) and Christou et al ( 2015 )]. However, discrepancies still exist in the field regarding the particular role of variations in the serotonin gene in moderating responses to environmental events [for a meta-analysis, see also Karg et al ( 2011 ) and Risch et al ( 2009 )].…”
Section: Introductionmentioning
confidence: 99%
“…As power in the alpha frequency band is inversely related to neural activity (stronger power indicating less activity; Allen et al, 2004), positive asymmetry values are considered to reflect greater left frontal activity i.e., greater left frontal asymmetry, whereas negative values reflect greater relative right frontal activity i.e., greater right frontal asymmetry. These differences in frontal EEG asymmetries have been hypothesized to arise from lateralized cortical and subcortical innervation by neurotransmitter (dopamine and serotonin) systems (Davidson, 1995; Wacker et al, 2013) and are modulated by variation in serotonin transporter-linked polymorphic region genotypes in healthy young children (Christou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%